Determinants of Inflation, Exchange Rate, and Output in Nigeria - Kuijs, Louis (IMF Working Papers; Working Paper, 1998)
This paper presents a macroeconomic model of the Nigerian economy. The long-run relationships pertaining to the markets for money, foreign exchange, and (non-oil) output are estimated. Subsequently, dynamic equations are estimated for the price level, the real exchange rate, and output. The results are instrumental in explaining the dramatic developments on the foreign exchange market during 1983-86 and 1992-94, the secular depreciation of the real exchange rate since 1985, and the rise and fall of inflation during 1991-97. The methodology could usefully be applied to other economies whose exports are insensitive to exchange rate movements (e.g., other oil-based economies).